2017
DOI: 10.1186/s13059-017-1212-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rare and low-frequency genetic variants in common disease

Abstract: Despite thousands of genetic loci identified to date, a large proportion of genetic variation predisposing to complex disease and traits remains unaccounted for. Advances in sequencing technology enable focused explorations on the contribution of low-frequency and rare variants to human traits. Here we review experimental approaches and current knowledge on the contribution of these genetic variants in complex disease and discuss challenges and opportunities for personalised medicine.Electronic supplementary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
231
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(238 citation statements)
references
References 152 publications
(183 reference statements)
5
231
0
2
Order By: Relevance
“…Individuals carrying rare alleles may show survival advantage against severe infection disease, for virus may adapt to the most frequent alleles in certain population (Trachtenberg et al, ). Moreover, genome‐wide association studies indicated that not only common variants were associated with complex traits (MAF > 5%), but some mutations with low frequency (MAF 1%–5%) or even rare genetic variants (typically defined to occur in less than 1% of the population) were also associated with complex diseases (Bomba, Walter, & Soranzo, ). So, we deduced that different HLA alleles may either associate with protection or susceptibility to CHC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals carrying rare alleles may show survival advantage against severe infection disease, for virus may adapt to the most frequent alleles in certain population (Trachtenberg et al, ). Moreover, genome‐wide association studies indicated that not only common variants were associated with complex traits (MAF > 5%), but some mutations with low frequency (MAF 1%–5%) or even rare genetic variants (typically defined to occur in less than 1% of the population) were also associated with complex diseases (Bomba, Walter, & Soranzo, ). So, we deduced that different HLA alleles may either associate with protection or susceptibility to CHC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Such technologies are promising, and have accelerated the understanding of other diseases . Rare variants may play an important role in chronic disease . Indeed, discovery of rare, protective variants for CVD has already resulted in successful development of cholesterol‐lowering drugs that mimic human mutations .…”
Section: New In Silico and Genomic Approaches To Understanding Osamentioning
confidence: 99%
“…Common variants are believed either to have small effect sizes or to be neutral. However, increasing evidence suggest that a modifier role of apparently neutral variants cannot be excluded …”
Section: Phox2b Gene Variantsmentioning
confidence: 99%